Type 1 Diabetes Mellitus in Children: Diagnosis and Management - Rike Delya Rizkina; Ananda Rizkia; Donna Diva Widyantari; Ghina Syafinatunnajah; Grandis Cristagalli; Irsyadina Hasana Bharata; Izza Mufida; Yoga Pamungkas Susani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Diabetes is a chronic metabolic disease characterized by increased blood sugar levels over time. This disease is caused by the presence of impaired insulin secretion, impaired insulin action, or both. The method used in writing this article is literature study. The literature study was carried out by searching published articles regarding the diagnosis and management of type 1 diabetes mellitus (T1DM) in children. Diagnosis is determined based on typical symptoms including polydipsia, polyuria, and decline body weight accompanied by blood sugar measurements. Components of managing T1DM (Type 1 Diabetes Mellitus) including (1) education; (2) insulin administration; (3) diet management; (4) physical activity; (5) self-monitoring; and (6) psychosocial therapy. Management of diabetes is necessary to achieve metabolic control optimally, preventing acute complications, microvascular or macrovascular complications, as well to improve the psychological aspects of patients and families.